Effect of protein concentration, pH, and ionic strength on the adsorption properties of rice bran protein concentrates at the oil-water interface - Abd Rahim, Farah Nadiah; Wan Ibadullah, Wan Zunairah; Saari, Nazamid; Mustapha, Nor Afizah; Brishti, Fatema Hossain; Mohammad Rashedi, Ismail Fitry; Shukri, Radhiah (Institution of Chemical Engineers, 2024)
Changes in protein concentration (PC), pH, and ionic strength (IS) influenced the physicochemical, structural, and rheological properties of emulsions made with natural emulsifiers. This study used rice bran protein concentrates (RBPC) to create RBPC-stabilized emulsions (RBP-E) and examined their emulsifying function by changing protein concentration, ionic strength, and pH. The results showed that increasing the PC resulted in a decrease in particle size, which caused the creaming rate and viscosity of RBP-E to increase, leading to the depletion flocculation phenomenon. Incorporating PC into the emulsion system improved adsorbed protein performance in particular pH, which positively correlates to the reduction of emulsion capacity in 3 % PC at neutral conditions. The introduction of IS decreased viscosity, enhanced solubility, and increased protein adsorption, thereby improving emulsion stability within a 3 % protein concentration. FTIR analysis revealed that as the pH shifted from 3 to 7, the α-helical structures increased, while β-sheet and β-turn structures reduced compared to untreated protein, decreasing surface hydrophobicity. Incorporating 1 % PC improved RBP-E performance at pH 7 and 0.5 M, while 2 % PC optimized emulsion capacity at 0.25 M and pH 3. Increasing PC from 1 % to 2 % improved emulsion stability and capacity by 35.4 and 34.4 %, respectively, at 0 M, particularly at pH 5. Therefore, the study concludes that IS, pH, and PC affect the adsorption of plant-derived protein at the O/W interface and enhance the emulsification capabilities of RBPC and the stability of RBP-stabilized emulsions. RPB-E can potentially be used in cake batter, ice cream mix, and margarine premix, a sustainable substitute for animal-based proteins.